2021
DOI: 10.1590/1807-3107bor-2021.vol35.0080
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Root ZXII, E-PEX and FIND apex locators in teeth with vital pulp: an in vivo study

Abstract: This research evaluated, in vivo, the accuracy of three electronic apex locators -EALs (Root ZXII, E-PEX and FIND) in teeth with vital pulp submitted to biopulpectomy, preserving the periodontal stump. For this study, 90 single-rooted teeth with extraction indication were selected. After positive pulpal cold sensitivity test, pulp chamber access was performed. The cervical and middle thirds of root canals were instrumented with Reciproc R25, and the K#15 file was used as a standard instrument to determine work… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 27 publications
1
2
0
Order By: Relevance
“…The accuracy of apex locator measurements increases as the file approaches the apical foramen. As in the present study, measurements at the 0.5 and 0.0 display numbers were considered accurate by other authors (Higa et al 2009;Piasecki et al 2018;Serna-Peña et al 2020;Cury et al 2021;Bernardes et al 2022). Other studies found more accurate results when EAL's measurements were obtained at 0.0 in the apical foramen, and worse results at 1mm short of the apical foramen (Saxena et al 2017;Adorno et al 2021).…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…The accuracy of apex locator measurements increases as the file approaches the apical foramen. As in the present study, measurements at the 0.5 and 0.0 display numbers were considered accurate by other authors (Higa et al 2009;Piasecki et al 2018;Serna-Peña et al 2020;Cury et al 2021;Bernardes et al 2022). Other studies found more accurate results when EAL's measurements were obtained at 0.0 in the apical foramen, and worse results at 1mm short of the apical foramen (Saxena et al 2017;Adorno et al 2021).…”
Section: Discussionsupporting
confidence: 85%
“…Several researchers have shown the accuracy of different apex locators to determine CRT, ranging from 89% to 97.8% for Root ZX II (Aguiar et al 2017;Saraf et al 2017;Cury et al 2021;Melo et al 2020) and from 92,5% a 95,6% for Romiapex A-15 (Saraf et al 2017;Melo et al 2020), both devices used in the present study. In the present study, the Root ZX II and RomiApex A-15 were accurate in locating the apical foramen and the distance of 0.5 mm close from the apical foramen in 93.5% of the times.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation